ANALISIS PERHITUNGAN CADANGAN KERUGIAN PENURUNAN NILAI PIUTANG DI PT. BANK SINAR HARAPAN BALI TAHUN 2011 - Arthana, Ida Bagus; Noviari, Naniekl; Noviari, Naniek (E-Jurnal Akuntansi, 2014)
This study analyzes the calculation of fund formation Allowance for impairment losses according to banking rules and according to the tax rules. Allowance for impairment on an allowance is established when the carrying value after impairment are less than the carrying amount of the initial. Recognition of allowance for impairment in accordance with banking regulations by Indonesian Banking Accounting Guidelines , while according to the tax rules on the terms of Regulation of the Minister of Finance No.81/PMK.03/2009. Fiscal correction is used to adjust for differences in the recognition of allowance for impairment in accordance with banking rules and according to the rules of taxation. Analysis of the data used is quantitative descriptive analysis. The analysis showed that there was no difference according to the allowance for impairment recognition PT. Bank Sinar Harapan Bali with banking rules. The same is shown in the application of fiscal correction to the allowance for impairment of PT. Bank Sinar Harapan Bali accordance with the tax regulations. This means recognition of allowance for impairment of PT. Bank Sinar Harapan Bali has appropriate banking regulation and taxation.
Keywords: Allowance for Impairment Losses; Banking Rules; Rules of Taxation; Fiscal Correction